The genus Typhonium (araceae) in flora of Vietnam - Du, Nguyen Van; Phuong, Vu Xuan (Academia Journal of Biology, 2015)
In the paper, the authors introduce the genus Typhonium in the world and in Vietnam with its studying history. The authors also introduce the key to identify the species of Typhonium in Vietnam. 13 species of Typhonium are mentioned with their nomenclature, distribution, biology, ecology and uses. In the paper, the first author mentiones to Typhonium laoticum as a new species for the Flora of Vietnam. However that he also notes that there is a little difference of the location of sterile flowers between the examined specimens and the type specimens.